Extended-Spectrum Beta-Lactamase Producing-Escherichia coli Isolated From Irrigation Waters and Produce in Ecuador - Montero, Lorena; Irazabal, Jorge; Cardenas, Paul; Graham, Jay P.; Trueba, Gabriel (Frontiers in Microbiology, 2021)
In cities across the globe, the majority of wastewater – that includes drug resistant and pathogenic bacteria among other contaminants – is released into streams untreated. This water is often subsequently used for irrigation of pastures and produce. This use of wastewater-contaminated streams allows antibiotic-resistant bacteria to potentially cycle back to humans through agricultural products. In this study, we investigated the prevalence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli isolated from produce and irrigation water across 17 provinces of Ecuador. A total of 117 vegetable samples, 119 fruit samples, and 38 irrigation water samples were analyzed. Results showed that 11% of the samples were positive for E. coli including 11 irrigation water samples (29%), and samples of 13 vegetables (11%), and 11 fruits (9%). Among the 165 E. coli isolates cultured, 96 (58%) had the ESBL phenotype, and 58% of ESBL producing E. coli came from irrigation water samples, 11% from vegetables, and 30% from fruits. The blaCTX–M–55, blaCTX–M 65, and blaCTX–M 15 genes were the most frequently found gene associated with the ESBL phenotype and coincided with the blaCTX–M alleles associated with human infections in Ecuador. Three isolates had the mcr-1 gene which is responsible for colistin resistance. This report provides evidence of the potential role of irrigation water in the growing antimicrobial resistance crisis in Ecuador.